Desenvolvimento de uma nova liga quaternária Ti25Ta25Nb4Sn para aplicações biomédicas - Marucci, Renan [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The increasing use of biomaterials in biological systems such as body environment has required studies to develop new materials that when used in specific functions, efficiently satisfy what they have been designated for, prostheses and dental implants. The use of titanium and its alloys grew exponentially because of this excellent properties such as high corrosion resistance, biocompatibility and low elasticity modulus. However, these materials can be corroded when exposed to body fluids. The release of metal ions can produce some toxicity, like NiTi and Ti6Al4V alloys. In this study, a new quaternary alloy with noncytotoxic elements Ti, Ta, Nb and Sn was processed and evaluated. The casting process of the metals was obtained an arc melting furnace with inert atmosphere (argon). The obtained ingots were submitted to an homogenization heat treatment (950 °C for 24 hours with slow cooling inside the furnace) and then cold forged in a rotary forge with subsequent solubilization and stabilization heat treatment. At each stage of the process, a sample was taken for microstructural analyses (optical microscopy and x-rays diffraction) and mechanical characterization of microhardness and corrosion resistance (open circuit potential and potentiodynamic polarization). The samples showed predominance of the β phase in this microstructure, microhardness of 184 HV, and a higher corrosion resistance than Ti CP and similar to the quaternary alloy Ti25Ta25Nb3Sn. Therefore, the Quaternary alloy Ti25Ta25Nb4Sn presented satisfactory results for biomedical applications

O crescente uso dos biomateriais em sistemas biológicos como o corpóreo, tem requerido estudos para desenvolvimento de novos materiais que, ao serem empregados em funções específicas, satisfaçam de modo eficiente ao que foram projetados, como por exemplo próteses e implantes dentários. Com isso, o uso do titânio e suas ligas cresceu de forma exponencial devido as suas excelentes propriedades como elevada resistência à corrosão, biocompatibilidade e baixo módulo de elasticidade. (Porém, estes materiais podem ser corroídos quando expostos em ambiente corpóreo. A liberação de íons metálicos pode produzir certa toxicidade, assim como as ligas NiTi e Ti6Al4V). Nesse estudo, uma nova liga quaternária com elementos não citotóxicos Ti, Ta, Nb e Sn, foi processada e avaliada. Para isso, os elementos foram fundidos em forno a arco voltaico em atmosfera inerte de gás argônio. Os lingotes obtidos foram submetidos a tratamento térmico de homogeneização (950 °C por 24 horas com resfriamento lento no forno) e então forjados a frio em forja rotativa com tratamento térmico posterior de solubilização. Em cada etapa do processo, foi retirada uma amostra para a realização de análises microestruturais (microscopia óptica e difração de raios-X) e para caracterização mecânica de microdureza e de resistência à corrosão (potencial em circuito aberto e polarização potenciodinâmica). As amostras apresentaram predominância da fase β em sua microestrutura, microdureza de 184 HV, e resistência à corrosão maior que o Ti CP e próxima a liga quaternária Ti25Ta25Nb3Sn. Sendo assim, a liga quaternária Ti25Ta25Nb4Sn apresentou resultados satisfatórios para possíveis aplicações biomédicas.
Development of new quaternary alloy Ti25Ta25Nb4Sn for biomedical applications
Keywords: Biomaterials; Titanium alloys; Quaternary alloys; Biomedical applcations; Biomateriais; Ligas de titânio; Ligas quaternárias; Aplicações biomédicas; Materiais biomédicos; Sistemas biológicos